Effectiveness of STEAM-based blended learning on students’ critical and creative thinking skills - Agnesi Sekarsari Putri; Zuhdan Kun Prasetyo; Lusila Andriani Purwastuti; Anti Kolonial Prodjosantoso; Himawan Putranta (Institute of Advanced Engineering and Science, 2023)
The critical and creative thinking skills of Indonesian students are relatively low from countries in the Malay family such as Malaysia and Singapore. This research aims to improve students’ critical and creative thinking skills through the use of Science, Technology, Engineering, Art, Mathematics (STEAM) based blended learning. This research is a quasi-experimental study using a nonequivalent pretest-posttest control-group design. The sample consists of 180 junior high school students in Yogyakarta, Indonesia. The samples in this study are 90 experimental class students and 90 control class students selected by random sampling cluster techniques because the selected samples come from individual groups or clusters. The instrument in this study consists of six questions in the form of essay questions. Test questions are analyzed using the gain score test and Kruskal-Wallis with SPSS 22. The results show steam-based blended learning can improve critical and creative thinking skills on all indicators with medium to high categories. The improvement of students’ critical and creative thinking skills in experimental classes is higher than that of the control class. In addition, there are differences in learning outcomes between control classes and experimental classes. STEAM-based blended learning can be an alternative for teachers to solve the problem of low critical and creative thinking skills.